The Influence of Dividends on the Earnings Quality (Empirical Study on Manufacturing Firms Listed on the Indonesia Stock Exchange 2016-2020) - Faiz Luthfi Saka; Andrian Budi Prasetyo (AFEBI Accounting Review, 2022)
This study aims to examine the effect of dividends on earnings quality in manufacturing sector firms listed on the Indonesia Stock Exchange 2016-2020, because there are several cases of manipulation of financial statements by firms that have been listed on Indonesia Stock Exchange, such as PT Garuda Indonesia.. In this study, the research model used is to use several dividend proxied as independent variables such as dividend payments, dividend size, dividend changes, dividend persistence and earnings quality as the dependent variables proxied by three models, namely absolute value of discretionary accruals (ADA), absolute value of accrual quality (AAQ) and accrual quality (AQ). The population used in this study are manufacturing firms listed on the Indonesia Stock Exchange in the 2016-2020 period. The selected sample is 450 financial statements consisting of 81 manufacturing firms that are in accordance with the research criteria. In testing the hypothesis using regression analysis. The results show that dividend payments, increasing the amount of dividends distributed and dividend persistence have a significant and negative effect on earnings quality as proxied by ADA and AAQ and AQ. However, dividend size does not have a significant effect on earnings quality.